PENGARUH SISTEM E-PERFORMANCE TERHADAP KINERJA DAN KOMPENSASI PEGAWAI NEGERI SIPIL - Syafrina, Muhairiyah; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research has been conducted at Dinas Tenaga Kerja Kota Surabaya which is located on Jalan Jemursari Timur II No. 2 Surabaya. The e-performance system has a role in monitoring the performance of civil servants (PNS) which is based technology to find out the performance of the employees either good or bad can be known based on the implementation of the basic tasks and functions in accordance with their structural position and it is supported by giving fair and appropriate compensation in accordance with each competency. This research has been done by using saturated sampling and 69 people have been selected as samples by using questionnaire survey methods, interview and the secondary data is correlated to the mission and the vision of the organization. After all questionnaires have been distributed 60.87% which are 42 questionnaires have returned. The result of the research shows that based F test has significant influence to the e-performance system and the performance and the compensation of civil servants (PNS) with its significance value is 0.000. Meanwhile, the individual (t test), independent variable has significant influence to the performance and the compensation i.e.: quality aspects, quantity aspects, and work behavior aspects. Moreover, the effectiveness aspects does not have any significant influence to the performance and the compensation due to the ability of civil servants in completing their work is not compatible with the schedule of implementation of the work plan, and it will have an impact on the compensation that has been received by civil servants will not be maximized.Keywords: e-performance System, Performance, Compensation